Bridging The Gap in Non-Process Energy Management: A Comprehensive Audit of A Power Plant Site Office in Power Generation Facilities Linked to Oil and Gas Operations - Mohd Nor, Norfakhira; Razali, Mohd Azahari; Adha Narrudin, Nur Syafiqah; Suzuki, Masataro; Tarmizi Nasir, Ahmad; Akhyan, Amnur (Testing Center for Oil and Gas LEMIGAS, 2026)
Energy efficiency research in oil and gas and power generation facilities has predominantly focused on core process systems, while non-process energy consumption in ancillary and administrative buildings remains under- represented in both regional and international literature. Existing building energy audit studies largely emphasise standalone commercial and institutional buildings, offering limited insight into site offices embedded within industrial facilities operating under extended schedules and tropical climatic conditions. This study addresses this gap by presenting a comprehensive non-process energy audit of a site office supporting a coal-fired power generation facility linked to oil and gas operations in Malaysia. The audit follows Malaysian Standard MS1525:2019 and integrates two years of electricity consumption data (April 2023–March 2025), Building Energy Intensity (BEI) benchmarking, end-use load apportioning, and indoor environmental quality (IEQ) assessment. The seasonal analysis confirmed that electricity consumption is strongly influenced by climate-driven cooling demand, with higher peaks occurring during hotter months. However, reductions in base-load consumption during milder periods reveal opportunities for improved operational efficiency and highlight the importance of distinguishing climate effects from controllable energy use when interpreting performance in industrial office environments. The site office recorded a BEI of 172.7 kWh/m²/year, exceeding the MS1525;2019 benchmark of 135 kWh/m²/year and lying at the upper range of values reported for conventional office buildings in tropical climates. HVAC systems dominate electricity consumption (55%), followed by lighting (24%) and general equipment (14%), indicating higher cooling dependency than typically observed in non-industrial office studies. Visual inspection revealed widespread over-illumination, while IEQ assessment identified temperature fluctuations and intermittent CO₂ exceedances, reflecting inconsistencies in environmental control. Collectively, these findings indicate that inefficiencies arise from the combined effects of HVAC operation, lighting design, and control strategies. Addressing these areas holistically offers potential to reduce BEI, flatten peak demand, and improve occupant comfort, while supporting integrated industrial energy management under Malaysia’s NEEAP and EECA 2024.